Interjections in Biblical Aramaic: A Radial Model - Andrason, Alexander W. (Aramaic studies, 2020)
This article examines the lexical class of interjections in Biblical Aramaic through the framework of an interjectional prototype and its functional (semantic and pragmatic) and formal (phonetic, morphological, and syntactic) characteristics. The authors analyse eight interjectional lexemes or constructional patterns, attested in twenty-four uses, for their compliance to the canonical prototype. The evidence reveals significant variation in the interjections’ canonicity: high canonicity in primary interjections, semi-canonicity in nearly primary interjections, and low canonicity in secondary interjections.